Priming of supernatural agent concepts and agency detection - van Elk, Michiel (Religion, brain & behavior, 2016)
In evolutionary approaches to religion it is argued that belief in supernatural agents is strongly related to a perceptual bias to over-detect the presence of agents in the environment. We report five experiments that investigate whether processing concepts about supernatural agents facilitates agency detection. Participants were presented with point-light stimuli representing unscrambled or scrambled biological motion, or with pictures of unscrambled or scrambled faces, embedded in a noise mask. Participants were required to indicate for each stimulus whether it represented a human agent or not. Each trial was preceded by a supernatural agent prime, a human agent prime, or an animal prime. Our results showed that primes referring to humans facilitated the detection of agency. More importantly, however, results did not reveal a general effect of supernatural priming on agency detection. In three experiments, a moderating effect of religiosity was observed: supernatural agent primes had a differential effect for religious compared to non-religious participants on agency detection biases and the speed of responding to agent-like stimuli. These findings qualify the relation between supernatural beliefs and agency detection and suggest that when supernatural agent concepts have been acquired through cultural learning, these concepts can modulate agency-detection biases.